Small-Scale Chemistry Experiment in Guided Inquiry Learning to Improve Concept Understanding and Science Process Skills - Zahronada, Afifa Ayu; Cahyono, Edy; Sumarti, Sri Susilogati (Universitas Negeri Semarang, 2025)
This study aims to analyze small-scale chemistry in guided inquiry to improve the relationship between students' conceptual understanding and science process skills. The research method used is a quasi-experimental design with a pretest-posttest nonequivalent control group design. The sample of this study consisted of two classes: the experimental class, which used small-scale chemistry in guided inquiry, and the control class, which employed conventional learning. The instruments used included a test (two-tier test) to measure conceptual understanding and observation sheets to measure science process skills. Data analysis was carried out using normality tests, homogeneity tests, t-tests, and Pearson correlation tests. The study's results showed a significant increase in understanding and science process skills in the experimental class compared to the control class. The increase in conceptual understanding was evident from the hypothesis test, with the N-gain value of the experimental class at 0.6 (moderate) and the control class at 0.29 (low). Meanwhile, the science process skills obtained t-test results and observation sheets, with an average of